Word-of-Mouth for Traditional Cuisine: A Brand Identity of Cucur Endolita Barokah Cakes - Meisy Septia Muzdalifah; Siti Khumayah; Aghnia Dian Lestari (Interdiciplinary Journal and Hummanity (INJURITY), 2026)
Word of mouth regarding traditional cuisine is an effective marketing strategy for introducing a business brand to potential customers, as it originates from consumers who share their firsthand experiences of trying the product. Recommendations based on personal experience are considered more trustworthy and authentic than digital advertisements. The purpose of this study is to examine the word-of-mouth process at the Kue Cucur Endolita Barokah SME in building brand identity. The research method employed a descriptive qualitative approach through in-depth interviews with the business owner, resellers, customers, and consumers to examine the word-of-mouth processes and strategies in shaping the brand identity of Kue Cucur Endolita Barokah. The results of the study indicate that word of mouth has proven highly effective in building the brand identity of Kue Cucur Endolita Barokah through the implementation of five interrelated elements of word of mouth, namely: credible talkers, such as resellers, customers, and family members; topics of discussion that focus on texture, taste, and authentic palm sugar (gula aren) as the main ingredient; tools of communication that include direct interaction and WhatsApp; taking part, which involves direct communication and WhatsApp interactions with quick responses and friendly service; and tracking, that is, relationship management through the maintenance of good connections with consumers. Furthermore, the role of word of mouth extends beyond being merely a promotional tool; it also serves to strengthen brand image and affirm the authenticity of the product.